Pharmacological effects of Chatuphalatika in hyperuricemia of gout - Vilasinee Hirunpanich Sato; Bunleu Sungthong; Prasob-Orn Rinthong; Narawat Nuamnaichati; Supachoke Mangmool; Savita Chewchida; Hitoshi Sato (Taylor & Francis Group, 2018)
Context: Chatuphalatika (CTPT), is a Thai herbal formulation mixture of Phyllanthus emblica Linn. (Euphorbiaceae), Terminalia belerica Linn. (Combretaceae), T. chebula and the fruit of T. arjuna (Roxb.) Wight & Arn. CTPT is considered to exert anti-inflammatory and antihyperuricemic effects, but there have been no reports to demonstrate these pharmacological effects in a quantitative manner. Objectives: To investigate the antioxidative, anti-inflammatory and antihyperuricemic effects of CTPT. Materials and methods: Antioxidant activities of CTPT extracts were measured in vitro by DPPH, ABTS and FRAP assays, and anti-inflammatory effect by measuring inflammatory mediator production induced by lipopolysaccharide (LPS) in RAW264.7 macrophages. The mechanism of the hypouricemic effect was investigated using oxonate-induced hyperuricemic ddY mice treated with oral administrations of CTPT at 250, 500 and 1000 mg/kg. Results: Antioxidant activities of CTPT measured by ABTS and FRAP assays were 1.35 g TEAC/g extract and 10.3 mmol/100 g extract, respectively. IC50 for the inhibition of DPPH radical was 13.8 µg/mL. CTPT (10 µg/mL) significantly downregulated the mRNA expression of TNF-α and iNOS in RAW 264.7 cells. Lineweaver-Burk analysis of the enzyme kinetics showed that CTPT inhibited xanthine oxidase (XOD) activity in a noncompetitive manner with the Ki of 576.9 µg/mL. Oral administration of CTPT (1000 mg/kg) significantly suppressed uric acid production by inhibiting hepatic XOD activity, and decreased plasma uric acid levels in hyperuricemic mice by approximately 40% (p < 0.05). Conclusions: This study demonstrated for the first time the antioxidative, anti-inflammatory and antihyperuricemic effects of CTPT in vivo and in vitro, suggesting a possibility of using CTPT for the treatment of hyperuricemia in gout.